cómic online como recurso didáctico en el aula. Webs y aplicaciones para móviles - Onieva López, Juan Lucas (Huarte de San Juan. Filología y Didáctica de la Lengua, 2015)
The students’ need for being motivated to improve their implication in their own formation has obliged many teachers to look for new resources and a continue formation. As can be inherited from the high number of studies quoted in this article, many of them have considered the comic as an excellent way for the students to study and research about different scholar topics. Regarding that the use of the information and communication tools are going to be improved in the future as a didactic resource, we have tried to propose a wide range of webs and mobile applications that makes an effective use of the comic in the classroom. In addition, we have highlighted a number of tools referred to the evaluation.